Political discussions lead to political efficacy among students in Indonesia. Issue 1 (March 2023) - Mashud, Mustain; Ida, Rachmah; Saud, Muhammad
Student unions based on religious and political affiliations are of paramount importance in political decision-making around the globe and in Indonesia particularly. The involvement of youth in political arenas and narrative building has become a debated topic among academicians, scholars and policymakers. In the context of Indonesia, the association of youth with religious groups has been seen as very important for engaging them in capacity-building initiatives (students in particular) and in political activities by mobilizing them with general communities. The present study examines the phenomenon of political efficacy through the political participation of youth associated with different religious and political groups. In consideration of the nature of the study, the present research tried to accomplish the desired outcomes by employing a quantitative research design and carrying out surveys. For that purpose, a self-administered questionnaire was developed with the help of literature for gathering data. The data were gathered from students and the general public, focusing on the premise that political discussion and religious group affiliation can be instrumental for political efficacy. The research found that the affiliation of students with religious groups has a strong impact on their involvement in political activities. Along with various political and religious factors, social media is considered a decisive factor in forming youth's political opinions and developing a sense of community engagement as well as practising their political rights. The data also show that there is a significant relationship between political efficacy and social media, highlighting that the participation of students in political discussion leads to political efficacy by mobilizing youth with general communities to create a discursive political environment.